2023
DOI: 10.2147/idr.s401807
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Characteristics of Clinical Distribution and Resistance Trends of Carbapenem-Resistant and Extended-Spectrum β-Lactamase Klebsiella pneumoniae Infections: 2014–2022

Abstract: Through long-term and large sample size statistical analysis, we revealed the pattern of Klebsiella pneumoniae (KP) infection and drug resistance and provided epidemiological data for the treatment and prevention and control of multidrug-resistant bacterial infection in our hospital. Patients and Methods: Strains were identified using the BD Phoenix TM 100 system, minimal inhibitory concentration of antibiotics were determined by the broth method, and data were statistically analyzed using WHONET 5.6 and SPSS2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…We found that the rate of TMP/SMX resistance for CRKP isolates was about two-fold lower in 2021 compared to 2019. A similar study conducted in China from 2014 to 2022 found an approximately stable level of resistance to TMP/SMX of about 23% for Klebsiella pneumoniae isolates but reported an increase in the resistance rate to TMP/SMX for CRKP isolates between 2019-2021, from 10.5% to 65.6% [34]. Another study conducted in China showed a relatively constant rate of TMP/SMX resistance for Klebsiella pneumoniae isolates of about 24% from 2017 to 2020 [35].…”
Section: Discussionmentioning
confidence: 90%
“…We found that the rate of TMP/SMX resistance for CRKP isolates was about two-fold lower in 2021 compared to 2019. A similar study conducted in China from 2014 to 2022 found an approximately stable level of resistance to TMP/SMX of about 23% for Klebsiella pneumoniae isolates but reported an increase in the resistance rate to TMP/SMX for CRKP isolates between 2019-2021, from 10.5% to 65.6% [34]. Another study conducted in China showed a relatively constant rate of TMP/SMX resistance for Klebsiella pneumoniae isolates of about 24% from 2017 to 2020 [35].…”
Section: Discussionmentioning
confidence: 90%
“…We are glad to receive comments on our recent publication in Infection and Drug Resistance from three authors. 1 They gave professional suggestions and comments on the article, which will guide our follow-up research. As they suggested, although it is appropriate for us to conduct phenotypic screening experiments on carbapenem-resistant Klebsiella pneumoniae (CRKP) through the MIC values of imipenem and meropenem, we should add confirmation experiments on carbapenem enzyme in our experiments, which will help improve the accuracy of laboratory reports.…”
Section: Dear Editormentioning
confidence: 99%
“…We have read the paper by Wang et al on Long Term Characteristic of Clinical Distribution and Resistance Trends of Carbapenem-Resistant and Extended-Spectrum β-Lactamase Klebsiella Pneumoniae Infections. 1 . We congratulate the authors for providing data in the form of an overview of Klebsiella pneumoniae (KP) infection patterns and KP resistance to several antibiotics, which are useful for the treatment and prevention and control of bacterial infections that are resistant to various antibiotics used in hospitals.…”
Section: Dear Editormentioning
confidence: 99%
“…3 In the study by Wang et al, they conducted strain identification using the BD PhoenixTM100 system in which the minimum inhibitory concentration of antibiotics was determined by the broth method. 1 The method used is appropriate, however we recommend continuing with a modified carbapenem inactivation method in which the isolates studied are determined by multilocus sequence types, and the presence of carbapenemase genes and virulence are examined using the polymerase chain reaction test. In addition, the modified carbapenem inactivation method (mCIM) and the EDTAcarbapenem inactivation method (eCIM) also help to determine the phenotype of the carbapenemase.…”
Section: Dear Editormentioning
confidence: 99%